Questions and more questions
Consider the following wff (∀y)(∃x)Q(x,y)→(∃x)(∀y)Q(x,y)
Find an interpretation to prove this wff is not valid
Find the flaw in the following "proof" of this wff.
I am not sure how to disprove this or where the flaw is.
This problem I know is invalid, again, I am not sure how to prove it is invalid.
(∀x)P(x) V (∃x) Q(x)→(∀x)[P(x) V Q(x)]
My textbook does not have answers to exercises in the back. Therefore, I have no way of knowing whether I am doing these problems correctly. I would like to see, hopefully correct solutions, so I know what I am doing and gain confidence.